Composite nano additive applied to polymer electrolyte and preparation method of composite nano additive

By adopting the composite nanoadditive MCN and using the porous structure of materials such as MXene and ZIF67, the shortcomings of polymer electrolytes in ionic conductivity and flame retardancy are solved, and a high-performance and safe solid-state battery is achieved.

CN119627264APending Publication Date: 2025-03-14NANJING TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411754941.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, additives have failed to effectively improve the safety and electrochemical properties of polymer electrolytes, especially in improving ionic conductivity and flame retardancy.

Method used

MXene nanosheets were prepared by hydrochloric acid etching and peeling, and combined with electrostatic assembly and ion etching methods, loaded metal organic frame ZIF67 and nickel ions were formed to form MCN composite nanoparticles with porous structures as modified additives for PEO/LiTFSI-based polymer electrolytes.

Benefits of technology

It significantly improves the ionic conductivity and flame retardancy of the electrolyte, improves the safety and electrochemical properties of polymer electrolytes, and is of guiding significance in the development of high-performance safe solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627264A_ABST
    Figure CN119627264A_ABST
Patent Text Reader

Abstract

The invention discloses a composite nano additive applied to a polymer electrolyte and a preparation method of the composite nano additive. The preparation method comprises the following steps: preparing an MXene dispersion liquid; preparing MXene (at) ZIF67 powder; preparing MXene (at) CoNi-LDH (layered double hydroxide) powder; titanium carbide (MXene) nanosheets are prepared through hydrochloric acid etching and stripping, then electrostatic assembly and ion etching methods are combined, a metal organic framework ZIF67 is loaded on the MXene nanosheets, then the ZIF67 is etched through nickel ions, MCN composite nanoparticles of a porous structure are obtained, MCN serves as a modified additive of PEO / LiTFSI-based polymer electrolyte, and the PEO / LiTFSI-based polymer electrolyte is prepared. And the ionic conductivity and flame retardance of the electrolyte are improved. The MCN composite nano additive disclosed by the invention has the functions of improving the ionic conductivity and flame retardant property of the polymer electrolyte, and has guiding significance on development and application of high-performance safe solid-state batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer electrolytes, in particular to a composite nano additive applied to polymer electrolytes and a preparation method thereof. Background Art

[0002] The electrolyte of lithium-ion batteries often uses flammable carbonate solvents, which have a high fire hazard. Safety issues have become one of the main obstacles to the application of lithium-ion batteries. Using polymer electrolytes to replace flammable electrolytes is an effective strategy to improve the safety of lithium-ion batteries.

[0003] Polymer electrolytes have good flexibility and easy processability, however, low ionic conductivity makes polymer electrolytes difficult to apply. Currently, a large number of studies have been devoted to improving the ionic conductivity of polymer electrolytes. For example, the Chinese patent with application number 201910983175.1 and invention name is a MXene-doped polymer solid electrolyte membrane and its application. MXene two-dimensional materials are added to high molecular polymers to improve the ionic conductivity, chemical stability and cycle life of the solid electrolyte membrane. However, polymer electrolytes still have the risk of flammability. Therefore, developing suitable additives for polymer electrolytes to improve their electrochemical properties and safety is of great significance for the manufacture of high-performance and high-safety solid-state lithium-ion batteries. Summary of the invention

[0004] In order to solve the problem that the additives in the prior art fail to improve the safety performance of polymer electrolytes, a composite nano additive applied to polymer electrolytes and a preparation method thereof are provided.

[0005] The present invention adopts the following technical solution:

[0006] A method for preparing a composite nano additive, comprising:

[0007] Step 1, preparing a MXene dispersion;

[0008] Step 2, preparing MXene@ZIF67 powder;

[0009] Dissolve cobalt nitrate hexahydrate powder in methanol to obtain solution A; dissolve 2-methylimidazole in methanol to obtain solution B, pour solution B into solution A to obtain a mixed solution of A plus B; add MXene dispersion to the mixed solution of A plus B; centrifuge and wash the product, and freeze-dry to obtain MXene@ZIF67 powder;

[0010] Step 3, preparing MXene@CoNi-LDH powder;

[0011] The MXene@ZIF67 powder was dispersed in ethanol to obtain solution C; nickel nitrate hexahydrate powder was dissolved in ethanol to obtain solution D; the mass ratio of MXene@ZIF67 powder to nickel nitrate hexahydrate powder was between 1:1 and 1:2; solution D was added to solution C to obtain a mixed solution of C and D; the product was centrifuged and washed, and freeze-dried to obtain MXene@CoNi-LDH powder, referred to as MCN.

[0012] Preferably, the method for preparing the MXene dispersion in step 1 is: first dissolving lithium fluoride powder in hydrochloric acid, adding Ti 3 AlC 2 powder and keep stirring; then centrifuge the product and wash the product with deionized water; finally, disperse the product in water and ultrasonicate it, and then place it in a centrifuge for centrifugal separation to obtain a MXene dispersion.

[0013] Specifically, the preparation method of the composite nano-additive comprises:

[0014] Step 1, preparing a MXene dispersion;

[0015] Step 2, preparing MXene@ZIF67 powder;

[0016] 4 g of cobalt nitrate hexahydrate powder was dissolved in 200 mL of methanol and stirred for 30 min to obtain solution A; 6 g of 2-methylimidazole was dissolved in 200 mL of methanol and stirred for 30 min to obtain solution B, solution B was poured into solution A and stirred for 12 h to obtain a mixed solution of A plus B; 200 mL of MXene dispersion was added to the mixed solution of A plus B and stirred for 12 h; the product was centrifuged and washed, and freeze-dried to obtain MXene@ZIF67 powder;

[0017] Step 3, preparing MXene@CoNi-LDH powder;

[0018] All the MXene@ZIF67 powder obtained in step 2 was dispersed in 200 mL of ethanol and ultrasonically dispersed for 30 min to obtain solution C. 8 g of Ni(NO) 2 6H 2 O was dissolved in 200 mL of ethanol and stirred for 30 min to obtain solution D; solution D was added to solution C to obtain a mixed solution of C and D; the product was centrifuged, washed, and freeze-dried to obtain MXene@CoNi-LDH powder, referred to as MCN.

[0019] Furthermore, the specific method for preparing the MXene dispersion in step 1 is:

[0020] First, 1g LiF was dissolved in 20mL 9M HCl solution and placed in a PP container; then 1g Ti 3 AlC 2 powder; stirring was maintained at 35°C for 24 h; the resulting solution was then washed with deionized water and centrifuged to a neutral pH; the collected product was further ultrasonically exfoliated in an argon flow ice bath and centrifuged at 3500 rpm to obtain a layered Ti 3 C 2 T x Nanosheet suspension, i.e. MXene dispersion.

[0021] A method for preparing a composite electrolyte with a composite nano-additive comprises: dissolving PEO powder, LiTFSI powder and MCN powder in acetonitrile, wherein the mixing mass ratio of the MCN powder is 3-12wt%, that is, the mass proportion of the MCN powder in the three powders is 3-12wt%; pouring the obtained uniform solution into a polytetrafluoroethylene mold, leaving it at room temperature to volatilize a solvent, and then putting it into a vacuum oven for drying, and then taking it out and quickly moving it into a glove box in an argon atmosphere to obtain a composite electrolyte.

[0022] The beneficial effects of the present invention are:

[0023] The present invention firstly obtains titanium carbide (MXene) nanosheets by hydrochloric acid etching and stripping, then combines the electrostatic assembly and ion etching methods, first loads the metal organic framework ZIF67 on the MXene nanosheets, and then etches ZIF67 by nickel ions to obtain MCN composite nanoparticles with a porous structure, and uses MCN as a modified additive for PEO / LiTFSI-based polymer electrolytes to improve the ionic conductivity and flame retardancy of the electrolyte. The MCN composite nano additive of the present invention simultaneously has the function of improving the ionic conductivity and flame retardancy of the polymer electrolyte, and has guiding significance for the development and application of high-performance and safe solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 SEM image of MXene nanosheets;

[0025] Figure 2 SEM image of MXene@ZIF67;

[0026] Figure 3 SEM image of MXene@CoNi-LDH(MCN);

[0027] Figure 4 SEM image of the cross section of PEO / LiTFSI-MCN electrolyte membrane;

[0028] Figure 5is the ionic conductivity of composite electrolytes with different contents at different temperatures;

[0029] Figure 6 It is a comparison of the charge and discharge cycle performance of the solid-state batteries of Example 2 and Example 6;

[0030] Figure 7 is a comparison of the combustion heat release of the electrolytes of Comparative Example 1 and Example 4 in a cone calorimetry test;

[0031] Figure 8 It is a comparison of the combustion smoke production of the electrolytes of Comparative Example 1 and Example 4 in the cone calorimetry test.

[0032] Fig. 9 Comparison of the release of CO toxic gas from combustion of PEO / LiTFSI and PEO / LiTFSI-9%MCN electrolytes in cone calorimetry test;

[0033] Fig.10 It is a schematic diagram of carbonized materials formed after the combustion of PEO / LiTFSI and PEO / LiTFSI-9%MCN, wherein a is a schematic diagram of carbonized materials formed after the combustion of PEO / LiTFSI, and b is a schematic diagram of carbonized materials formed after the combustion of PEO / LiTFSI-9%MCN. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical scheme and technical effect of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0035] Example 1

[0036] The preparation method of the composite nano additive comprises:

[0037] Step 1, MXene nanosheet preparation process:

[0038] 1g LiF was dissolved in 20mL 9M HCl solution and placed in a PP container. Then, 1g Ti was added to the mixed solution. 3 AlC 2 Powder. Stirring was maintained at 35°C for 24 h. The resulting solution was then washed with deionized water and centrifuged to a neutral pH. The collected product was further ultrasonically exfoliated in an argon flow ice bath and centrifuged at 3500 rpm to obtain layered Ti 3 C 2 T x Nanosheet suspension, i.e. MXene dispersion.

[0039] The dark green MXene suspension was freeze-dried to obtain MXene powder.

[0040] like Figure 1 , showing the SEM image of MXene nanosheets. After etching and ultrasonic exfoliation, the MXene nanosheets obtained have a smooth and flat surface and are about tens of microns in size, making them very suitable as a substrate for the attachment of other materials.

[0041] Step 2, MXene@ZIF67 preparation process:

[0042] Put 4g Co(NO) 3 6H 2 O was dissolved in 200 mL of methanol and stirred for 30 min to obtain solution A. Then 6 g of 2-methylimidazole was dissolved in 200 mL of methanol and stirred for 30 min to obtain solution B. Solution B was poured into solution A and stirred for 12 h. 200 mL of MXene dispersion (2 mg / mL) was added to the mixed solution of A and B, and stirring was continued for 12 h.

[0043] The product was centrifuged, washed, and freeze-dried to obtain MXene@ZIF67 powder.

[0044] like Figure 2 , showing the SEM image of MXene@ZIF67, regular dodecahedral ZIF67 particles with a size of 1 to 2 μm can be clearly found on the surface.

[0045] Step 3, MXene@CoNi-LDH preparation process:

[0046] All the MXene@ZIF67 powders prepared in step 2 were dispersed in 200 mL of ethanol and ultrasonically dispersed for 30 min to obtain solution C. 8 g Ni(NO) 2 6H 2 O was dissolved in 200 mL of ethanol and stirred for 30 min to obtain solution D. The obtained solution D was added to solution C and stirred for 12 h. The product was centrifuged, washed, and freeze-dried to obtain MXene@CoNi-LDH powder, referred to as MCN.

[0047] like Figure 3 , showing the SEM image of MCN. After etching, the ZIF67 particles have disappeared and MCN particles are obtained. Due to the support of the ZIF67 framework, the LDH on the surface of MCN has a large number of pores, giving it a higher specific surface area.

[0048] First, 2-methylimidazole and cobalt nitrate react to generate a ZIF67 organic metal framework with a dodecahedral structure, and then MXene is added to couple ZIF67 with MXene. The ZIF67 in the obtained MXene@ZIF67 composite particles has a regular dodecahedral framework structure, as shown in Fig. Figure 2; However, the solution with application number 202111188005.8 does not have such an effect. Compared with deionized water, using methanol as a solvent is conducive to the formation of the dodecahedral structure of ZIF67. ZIF67 has a framework structure, and when preparing MXene@CoNi-LDH in step 3, abundant pores supported by the framework can be formed, see Figure 3 , the porous structure is conducive to the adsorption of anions and improves the ionic conductivity of the electrolyte.

[0049] Example 2

[0050] In this embodiment, a composite electrolyte is prepared, wherein the mass proportion of MCN powder is 3 wt %, specifically:

[0051] 3.57g polyethylene oxide PEO, 0.97g lithium bis(trifluoromethanesulfonyl)imide LiTFSI and 0.14g MCN powder were dissolved in acetonitrile with a molar ratio of EO / Li of 24:1. The mixture was stirred continuously for 24h. The obtained uniform solution was poured into a polytetrafluoroethylene mold and allowed to stand at room temperature for 24h to evaporate the solvent. The solution was then placed in a vacuum oven and dried at 60°C for 24h. After being taken out, it was quickly moved into a glove box with an argon atmosphere. The obtained PEO / LiTFSI-MCN composite electrolyte membrane was cut into 19mm discs for standby use. The composite electrolyte is referred to as SPE.

[0052] In this embodiment, the molar ratio of EO / Li is 24:1, and other ratios may be selected in other embodiments. In this embodiment, the drying temperature is 60° C. and the drying time is 12 hours, which may also be adjusted, such as selecting a higher drying temperature and a shorter drying time.

[0053] Example 3

[0054] The only difference between this embodiment and embodiment 2 is that the mass proportion of MCN powder in this embodiment is 6wt%, specifically 3.46g PEO, 0.94g LiTFSI and 0.28g MCN powder.

[0055] Example 4

[0056] The only difference between this embodiment and embodiment 2 is that the mass proportion of MCN powder in this embodiment is 9wt%, specifically 3.35g PEO, 0.91g LiTFSI and 0.42g MCN powder.

[0057] Example 5

[0058] The only difference between this embodiment and embodiment 2 is that the mass proportion of MCN powder in this embodiment is 12%, specifically 3.24 g PEO, 0.88 g LiTFSI and 0.56 g MCN powder.

[0059] like Figure 4 As shown, the SEM image of the cross section of the PEO / LiTFSI-MCN electrolyte membrane obtained in Example 2-5, the electrolyte membrane thickness is about 100 μm.

[0060] Comparative Example 1

[0061] The only difference between this comparative example and Example 2 is that no MCN powder is added in this comparative example.

[0062] The MCN contents in the electrolytes of Comparative Example 1 and Examples 2-5 are 0wt%, 3wt%, 6wt%, 9wt% and 12wt%, respectively. The specific components are shown in Table 1. The electrolytes with MCN contents of 3wt%, 6wt%, 9wt% and 12wt% are named PEO / LiTFSI-3%MCN, PEO / LiTFSI-6%MCN, PEO / LiTFSI-9%MCN and PEO / LiTFSI-12%MCN, respectively.

[0063] Table 1 Components of PEO / LiTFSI-MCN electrolyte membrane

[0064] MCN content (wt%) PEO(g) LiTFSI(g) MCN(g) 0% 3.68 1 0 3% 3.57 0.97 0.14 6% 3.46 0.94 0.28 9% 3.35 0.91 0.42 12% 3.24 0.88 0.56

[0065] The ionic conductivity values ​​of composite electrolytes (SPE) with different MCN contents at different temperatures were tested, such as Figure 5 It can be found that the ionic conductivity of all SPEs gradually increases with the increase of temperature. Between 50 and 60 °C, due to the melting of PEO, the crystalline phase in the polymer transforms into the amorphous phase, which promotes the fluidity of the PEO segment at high temperature, so the ionic conductivity increases significantly. At all temperatures, the ionic conductivity of the PEO / LiTFSI-9%MCN sample is the highest among all SPEs, reaching 3.6×10 -4 S / cm, much higher than 3×10 of pure PEO / LiTFSI electrolyte -5 S / cm.

[0066] In summary, after adding MCN particles, MCN can reduce the crystallinity of PEO and promote the dissociation of lithium salt through physical and chemical effects such as Lewis acid-base and pore adsorption, so that the ionic conductivity of the polymer electrolyte is effectively improved.

[0067] The ionic conductivity test method belongs to the existing technology. The SS / SPE / SS button cell is assembled using a stainless steel gasket (SS). The test equipment is Chenhua CHI660E electrochemical workstation with a frequency range of 10 -2 ~10 5 Hz, in the temperature range of 20~80℃, after keeping each temperature for 1h, the electrochemical impedance spectroscopy (EIS) test was performed. The ionic conductivity calculation formula is:

[0068]

[0069] Where: L is the thickness of the electrolyte, R is the impedance, and S is the contact area between the electrolyte and the stainless steel sheet.

[0070] The electrolytes of Comparative Example 1 and Example 4 were made into 100×100×3 mm 3 The cone calorimetric combustion test was carried out with a heat flux of 35kW / m 2 , testing is prior art.

[0071] Test results such as Figure 7 , 8 As shown, Figure 7 The total heat release of pure PEO / LiTFSI is 66MJ / m 2 After adding 9wt% MCN particles, the total heat release was reduced to 44.75MJ / m 2 , which was reduced by 32.2%, indicating that MCN has a significant inhibitory effect on combustion heat release.

[0072] Figure 8 The total smoke production (TSP) of pure PEO / LiTFSI is 0.94m 2 After adding 9% MCN, TSP decreased to 0.46m 2 The reduction was 51.1%. This shows that MCN nanostructure has obvious advantages in reducing the smoke toxicity of PEO / LiTFSI.

[0073] Fig. 9 Comparison of the release of CO toxic gas from combustion of PEO / LiTFSI and PEO / LiTFSI-9%MCN electrolytes in cone calorimetry test.

[0074] In summary, the addition of MCN improves the flame retardant properties of PEO / LiTFSI electrolytes. The cone combustion test proves that MCN has a significant inhibitory effect on the release of heat, smoke, and CO toxic gases during the combustion of PEO / LiTFSI, which are reduced by 32.2%, 51.1%, and 80.5%, respectively. During combustion, the double hydroxide (CoNi-LDH) component in MCN will decompose and absorb heat, thereby reducing the temperature. In addition, the metal oxide (TiO 2 、NiO x 、CoO x), these metal oxides form dense blocks, and black carbonized substances can be seen inside, such as Fig.10 , indicating that metal oxides with Lewis acid properties promote carbonization through a catalytic mechanism and protect carbonized substances with a dense structure, so that some organic carbon does not participate in combustion, reducing the heat, smoke and toxic gas production of combustion.

[0075] If only MXene is added to the PEO / LiTFSI electrolyte, due to the flaky structure of MXene, the MXene will be stacked and agglomerated, and cannot be evenly dispersed in the polymer to form a barrier network, which cannot effectively block the release of combustible cracking gases. Therefore, the flame retardant effect will be worse than adding MXene@CoNi-LDH.

[0076] Example 6

[0077] 7g lithium iron phosphate LiFePO 4 (LFP) powder, 2g conductive carbon black and 1g PEO / LiTFSI powder (EO:Li=16) were mixed in a mass ratio of 7:2:1, 100mL acetonitrile was added as a solvent, and the slurry was obtained by grinding and dispersion. The slurry was coated on aluminum foil with a 400μm scraper and dried in a vacuum oven at 60℃ for 12 hours to obtain LiFePO 4 The present invention controls the mass loading of the positive electrode LFP to 2 mg / cm 2 The electrode is formed into a circular positive electrode with a diameter of 12 mm for assembling button batteries.

[0078] In this embodiment, lithium iron phosphate LiFePO 4 The mass ratio of (LFP) powder, conductive carbon black and PEO / LiTFSI powder is 7:2:1, and other mass ratios can be used in other embodiments. In this embodiment, the drying temperature is 60°C and the drying time is 12h, which can also be adjusted, such as selecting a higher drying temperature and a shorter drying time.

[0079] Example 7

[0080] Example of Supplementary Preparation of PEO / LiTFSI-9%MCN Battery

[0081] A 2032 specification button battery shell was used, and the stacking order from bottom to top was: negative electrode shell, lithium sheet, PEO / LiTFSI-9%MCN electrolyte membrane, LFP positive electrode sheet (Example 6), gasket, spring sheet, positive electrode shell. The stacked batteries were pressed to obtain a PEO / LiTFSI-9%MCN solid-state battery, and the battery was left to stand at 60°C for 12 hours for a cycle test.

[0082] The solid-state battery of Example 7 was subjected to a cycle performance test. The test method is the prior art. The full battery cycle performance test can evaluate the performance of the solid electrolyte in actual use. The cycle test was carried out in a 60°C environment. The battery test voltage range was 2.5 to 4.2V.

[0083] Figure 6 The charge and discharge cycle performance of the solid-state battery of Example 6 and Example 7 is compared. The discharge capacity of the pure PEO / LiTFSI battery at the 10th, 50th, 100th, 150th, 200th, 250th, and 300th cycles is 93.84, 113.51, 107.62, 89.72, 80, 54.74, and 49.63 mAh / g, respectively, while the discharge capacity of the PEO / LiTFSI-9%MCN battery at the corresponding number of cycles is 139.55, 159.88, 164.19, 153.47, 143.95, 132.51, and 129.16 mAh / g, respectively. After 300 cycles, the coulomb efficiency is 99.52%, and the capacity retention rate is 78.23%. Compared with pure PEO / LiTFSI, the capacity and cycle stability of the PEO / LiTFSI-9%MCN battery are greatly improved.

[0084] The battery performance is gradually optimized with the increase of MCN ratio (3wt%, 6wt%, 9wt%). When the MCN ratio reaches 12wt%, the battery performance is worse than that of the 9wt% battery. This is because the excess MCN will produce a barrier effect, hindering the movement of lithium ions.

[0085] In summary, it can be explained that the capacity performance and cycle stability of the LFP / SPE / Li full battery using PEO / LiTFSI-MCN are better.

[0086] It should be understood that parts not described in detail in this specification belong to the prior art.

[0087] The above combined with the accompanying drawings are only specific implementation methods and processes of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the art should understand that this is only an example, and various changes and substitutions can be made to this implementation method without departing from the essence of the present invention. The scope of the present invention is limited only by the attached claims.

Claims

1. A method for preparing a composite nano-additive, characterized in that: include: Step 1, preparing a MXene dispersion; Step 2, preparing MXene@ZIF67 powder; Dissolve cobalt nitrate hexahydrate powder in methanol to obtain solution A; dissolve 2-methylimidazole in methanol to obtain solution B, which is poured into solution A to obtain a mixed solution of A and B; add MXene dispersion to the mixed solution of A and B; centrifuge and wash the product, and freeze-dry to obtain MXene@ZIF67 powder; Step 3, preparing MXene@CoNi-LDH powder; MXene@ZIF67 powder was dispersed in ethanol to obtain solution C; nickel nitrate hexahydrate powder was dissolved in ethanol to obtain solution D; the mass ratio of MXene@ZIF67 powder to nickel nitrate hexahydrate powder was between 1:1 and 1:2; solution D was added to solution C to obtain a mixed solution of C and D; the product was centrifuged, washed, and freeze-dried to obtain MXene@CoNi-LDH powder, abbreviated as MCN.

2. The method for preparing a composite nano-additive according to claim 1, characterized in that: The method for preparing the MXene dispersion in step 1 is as follows: first, lithium fluoride powder is dissolved in hydrochloric acid, Ti3AlC2 powder is added to the mixture, and stirring is maintained; then the product is centrifuged and washed with deionized water; finally, the product is dispersed in water and ultrasonicated, and then placed in a centrifuge for centrifugal separation to obtain a MXene dispersion.

3. The method for preparing a composite nano-additive according to claim 1, characterized in that: include: Step 1, preparing a MXene dispersion; Step 2, preparing MXene@ZIF67 powder; 4 g of cobalt nitrate hexahydrate powder was dissolved in 200 mL of methanol and stirred for 30 min to obtain solution A. 6 g of 2-methylimidazole was dissolved in 200 mL of methanol and stirred for 30 min to obtain solution B. Solution B was poured into solution A and stirred for 12 h to obtain a mixed solution of A and B. 200 mL of MXene dispersion was added to the mixed solution of A and B and stirred for 12 h. The product was centrifuged, washed, and freeze-dried to obtain MXene@ZIF67 powder. Step 3, preparing MXene@CoNi-LDH powder; The entire MXene@ZIF67 powder obtained in step 2 was dispersed in 200 mL of ethanol and ultrasonically dispersed for 30 min to obtain solution C. 8 g of Ni(NO)2·6H2O was dissolved in 200 mL of ethanol and stirred for 30 min to obtain solution D. Solution D was added to solution C to obtain a mixed solution of C and D. The product was centrifuged, washed, and freeze-dried to obtain MXene@CoNi-LDH powder, referred to as MCN.

4. The method for preparing a composite nano-additive according to claim 3, characterized in that: The specific method for preparing the MXene dispersion in step 1 is: First, 1 g of LiF was dissolved in 20 mL of 9 M HCl solution and placed in a PP container. Then, 1 g of Ti3AlC2 powder was added to the mixed solution and stirred at 35 °C for 24 h. The resulting solution was then washed with deionized water and centrifuged to a neutral pH value. The collected product was further ultrasonically exfoliated in an argon flow ice bath and centrifuged at 3500 rpm to obtain layered Ti3C2T x Nanosheet suspension, i.e. MXene dispersion.

5. A method for preparing a composite electrolyte using a composite nano-additive, characterized in that: PEO powder, LiTFSI powder and MCN powder were dissolved in acetonitrile, wherein the mass ratio of MCN powder was 3-12 wt%, that is, the mass proportion of MCN powder in the three powders was 3-12 wt%; the obtained uniform solution was poured into a polytetrafluoroethylene mold, left at room temperature to volatilize the solvent, and then placed in a vacuum oven for drying. After taking out, it was quickly moved into a glove box with an argon atmosphere to obtain a composite electrolyte.

Citation Information

Patent Citations

  • MXene doped polymer solid electrolyte membrane and application thereof

    CN110739489A

  • A ternary nanocomposite flame retardant, a flame-retardant epoxy resin and its preparation method

    CN113845695B